The Implementation and the Effects of Regulatory Reform Past Experience and Current Issues - Gönenç, Rauf (OECD Publishing, 2003)
This article reviews trends, outcomes and issues in regulatory reform in OECD countries. First, it summarises the evidence on the evolution of regulatory environments and the economy-wide and sectoral effects of reforms (including privatisation) in both competitive and non-competitive industries in the past two decades. Turning to network industries, it then discusses the main policy issues raised by the need to adapt the regulation of the non-competitive segments of these industries to increasing competition in liberalised markets. It focuses on four topics that dominate the debate over regulatory reform: i) the move from command-and-control to incentivebased regulatory approaches relying on the removal of entry barriers in competitive markets, the adoption of price-cap mechanisms and the design of efficient and competitively-neutral charges for accessing the fixed networks of incumbents; ii) the pros and cons of structural measures such as privatisation, and vertical and horizontal separation of formerly integrated monopolies; iii) the ways to ensure that important non-economic objectives, such as universality of service, continue to be achieved in a more competitive environment at a minimum cost for society; and iv) the design of regulatory mechanisms and institutions that encourage best practice regulation